2010
DOI: 10.1007/s11999-010-1409-2
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Broken Knee Megaprostheses: New Solution to Old Problems

Abstract: Revisions of broken total knee megaprostheses, though technically difficult, have allowed patients reasonable function. We recommend design analysis for custom prostheses to point to areas of weakness. Breakages can be reduced by using titanium stems and filleting the junction or by having two-piece inserted stems. Incorporating these changes has reduced the failures in our experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…One year after surgery, all the children were back to normal school and the mean MSTS after physical rehabilitation was 26.3 (21)(22)(23)(24)(25)(26)(27)(28)(29). Knee flexion was up to 100°in six cases and between 60°and 80°in one case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One year after surgery, all the children were back to normal school and the mean MSTS after physical rehabilitation was 26.3 (21)(22)(23)(24)(25)(26)(27)(28)(29). Knee flexion was up to 100°in six cases and between 60°and 80°in one case.…”
Section: Resultsmentioning
confidence: 99%
“…Aseptic loosening, mechanical failure, metal fatigue, infections, soft tissue problems, dislocation, infection or periprosthetic fractures are the most common complications [1,2,6,15,21,22,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agarwal et al identified 28 breakages in 266 megaprosthetic knee arthroplasties [5]. In the great majority of the cases, the TMH-Nice (Tata Memorial Hospital new indigenous customized prosthesis) was affected.…”
Section: Discussionmentioning
confidence: 99%
“…This classification system was further specified including biological and expandable reconstructions by the International Society of Limb Salvage (ISOLS) [4]. With regard to structural failures, several reports have been published about different tumor prosthesis systems [2, 57]. …”
Section: Introductionmentioning
confidence: 99%